Neotype designations and nomenclatural actions for Apionidae described by Johann Ludwig Christian Carl Gravenhorst in 1807 (Coleoptera, Curculionoidea) - Giusto, Carlo (Zootaxa, 2015)
In accordance with the International Code of Zoological Nomenclature with the express purpose of clarifying the systematic status of some species, neotypes are designated for Apion atratum Gravenhorst, 1807, Apion chloris Gravenhorst, 1807, Apion longirostre Gravenhorst, 1807 and Apion pilosellum Gravenhorst, 1807. Three new synonymies are proposed: Perapion hydrolapathi (Marsham, 1802) = Apion atratum Gravenhorst, 1807, syn. n., Ischnopterapion virens (Herbst, 1797) = Apion chloris Gravenhorst, 1807, syn. n. and Eutrichapion vorax (Herbst, 1797) = Apion longirostre Gravenhorst, 1807, syn. n. The junior primary homonym Apion atratum Wagner, 1908 (non Gravenhorst, 1807) is replaced by Pseudopiezotrachelus gravenhorsti nom. n.